GraphoLearn India : the effectiveness of a computer-assisted reading intervention in supporting English readers in India - Patel, Priyanka (2018)
Illiteracy is still a critical problem in many parts of the developing world. India, with a population of over 1.3 billion individuals, has a literacy rate of only 72%. Those living in poverty are at an even higher risk of never achieving literacy due to limited access to quality education. With a strong push towards English education sweeping the country, those in poverty further struggle to learn a language which is foreign to them. Without access to quality education, these individuals are ultimately never given the chance to break the cycle of poverty. The aim of this study was to determine whether GraphoLearn, a computer-assisted reading intervention, could be used to support the English reading skills of struggling readers in India. Participants were 7-year-old, grade 3 students (N=30), who were attending an English-medium public school in Ahmedabad, India. English was not a native language for any of the students and all were reading at a level below that of grade 1 despite having attended school for 2 years. Half of the students played GraphoLearn (n=16) while the other half played a control math game (n=14) for 20-30 minutes a day, over a period of 8 weeks. GraphoLearn led to significant improvements in children's letter-sound knowledge, a critical factor in early reading development. Small to medium effects were also present for other tasks of reading and spelling. These results indicate that GraphoLearn has the potential to successfully support struggling readers of English in India, including those who are learning a non-native language and coming from at-risk backgrounds.